2006
DOI: 10.1093/molehr/gal020
|View full text |Cite
|
Sign up to set email alerts
|

The role of the testis-specific gene hTAF7L in the aetiology of male infertility

Abstract: The X-linked TAF7L gene is homologous to the autosomal transcription factor TAF7. Together with its testis-specific expression pattern, this might point to an important function in spermatogenesis. In order to analyse the involvement of the hTAF7L gene in the aetiology of male infertility, a total of 25 patients with maturation arrest of spermatogenesis have been analysed for the presence of mutations in this gene. Four alterations of the nucleotide sequence, with concomitant changes in the amino acid sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 6 publications
4
33
0
Order By: Relevance
“…Thus, it has been speculated that the human TAF7L gene may be essential for the maintenance of spermatogenesis (137). However, sequence analysis of infertile patients and controls revealed no clear association to male infertility (108,138).…”
Section: Taf7lmentioning
confidence: 94%
“…Thus, it has been speculated that the human TAF7L gene may be essential for the maintenance of spermatogenesis (137). However, sequence analysis of infertile patients and controls revealed no clear association to male infertility (108,138).…”
Section: Taf7lmentioning
confidence: 94%
“…Mutation screening of TAF7L in 25 men with non-obstructive azoospermia did not reveal mutations that are associated with infertility (Stouffs et al 2006b). Two studies indicated that a haplotype in USP26 (371insACA, 494T9C and 1423C9T) might be a risk factor for male infertility (Paduch et al 2005, Stouffs et al 2005.…”
Section: Implications Of X-linked Meiosis Factorsmentioning
confidence: 98%
“…In several genetic studies, two X-linked germ cellspecific genes (TAF7L and USP26) were screened for mutations in infertile men (Paduch et al 2005, Stouffs et al 2005, 2006b. Mutation screening of TAF7L in 25 men with non-obstructive azoospermia did not reveal mutations that are associated with infertility (Stouffs et al 2006b).…”
Section: Implications Of X-linked Meiosis Factorsmentioning
confidence: 99%
“…In addition to Y chromosome microdeletion and mutation of autosome genes, X chromosomes are also closely related to male fertility; however, the underlying molecular mechanisms are still unknown [3,5]. There has been an intensive search in such genes located on the X chromosome as men are hemizygous for this chromosome [6,7]. Nishimune et al [8] observed many genes on the X chromosome that are related to male infertility.…”
Section: Introductionmentioning
confidence: 99%